Organização do processo de trabalho das Equipes de ESF para o alcance das metas pactuadas dos indicadores do Programa Previne Brasil em Rio Grande, RS - Manke, Renata Tarouco (2022)
The study aimed to investigate the organization of the work process of the Family Health Strategy teams in Rio Grande (RS) to achieve the goals proposed by the Previne Brasil Program. For that, a qualitative approach was used through in-depth interviews with 11 coordinators of health units of the Family Health Strategy in the municipality. The interviews were recorded and carried out between July and August 2022, virtually, through the Google Meet platform. For the analysis of the interviews, transcription and subsequent coding and reading were carried out for methodical exploration of the excerpts from the text segments, generating record units, summarizing, in an analytical way, such segments, classifying them into thematic categories. The first category described the implementation of the Previne Brasil program; the second, monitoring the achievement of indicators; the third, the achievement of the indicator targets; the fourth, the importance of the completeness of the ESF teams and, finally, the fifth described the assessment of the achievement of goals. The findings allowed verifying that the planning of health actions to reach the goals of the Previne Brasil indicators is taking place, however the coordinators have questions and difficulties in monitoring and achieving them. Weaknesses were identified, with emphasis on the lack of service structure, equipment and personnel. In the end, this study seeks to sensitize management in the three spheres of government so that the process of qualification of health actions, within the territories, is periodically monitored and the teams can be guided with knowledge and exchanges about the achievement of the goals of the indicators.